WORKSHOP ON MAKING FINANCIAL STATEMENTS TO INCREASE DATA INDEPENDENCE IN THE DIGITAL ERA FOR INDONESIAN MSMES - Sumarsid Sumarsid; Hartatik Hartatik; Khaeruman Khaeruman; Ahmad Mukhlis; Suflani Suflani; Lilis Suryani (International Journal of Engagement and Empowerment, 2022)
In developing Small and Medium Micro Enterprises (MSMEs) it is necessary to know the  performance of  its business in view of its business financial statements.  The problem  that exists today  is that the  majority of MSMEs in Indonesia do not make financial statements because of various things, namely busyness in trying and not knowing how to make   financial statements. The results of interviews and surveys to 100 MSMEs  in Indonesia  in   February are that  almost all MSMEs  do not know how to make basic or  simple  financial statements.  So we as Pengabdi aim to provide knowledge of making simple   financial statements by providing training and assistance in making digital  financial statements with the help of Smartphones,  due to the  flexibility of  time and place in its manufacture.  The method provided by   way of 1.Training in making simple  financial statements for MSMEs, 2.Training and assistance in making android-based  digital  accounting in Smartphones. The results of the workshop of  MSME  participants who follow the spirit of practice and can make  financial statements on  their respective Smartphones